PENGARUH METODE LATIHAN DIAMOND PASS TERHADAP PASSING CONTROL PESERTA EKSTRAKURIKULER FUTSAL SMKN 1 MOJOSONGO - Dwi Yudha Kurniawan; Wiga Nurlatifa Romadhoni (Universitas Negeri Semarang, 2023)
This research is motivated by the passing technique in futsal which is still not mastered by futsal extracurricular students at SMKN 1 Mojosongo, meanwhile, passing is one of the basic techniques of playing futsal that is needed by every player. The research objective was to determine the effect of the diamond pass training method on the passing control of futsal extracurricular participants at SMKN 1 Mojosongo. The study used an experimental method with a one group pretest-posttest design. The study population consisted of 30 futsal extracurricular participants at SMKN 1 Mojosongo, while the sample for this study consisted of 20 participants obtained by simple purposive sampling method. The research results from hypothesis testing using the t test were processed using the SPSS version 25 application with a significance level of 0.05 with a result of 0.004> 0.05 so that Ho was rejected and Ha was accepted. The conclusion of the study is that there are differences in the effect of the diamond pass training method on the passing control of futsal extracurricular participants at SMKN 1 Mojosongo. Suggestions to trainers, to use diamond pass training in the program to improve passing control abilities.